Hazards of Platelet Transfusion - Das , Subhashis; Nikhil; Khichariya , Gaurav; Amrutha , T.; Sinha , Snigdha (Research Advances in Microbiology and Biotechnology Vol. 5, 2023)
Introduction: Antibody screening followed by nucleic acid amplification techniques in blood donor screenings have decreased nowadays but bacterial contamination still remains a key problem in Blood banking. Particularly platelets are affected due to constant suitable environment for bacteria to grow such as storage temperature and composition of platelet concentrates. Materials and Methods: Various methods are implied to evaluate contaminated platelet units. Quantitative/qualitative assessment by number of Colony forming units infused ,swirling phenomenon and microscopic evaluation of blood and its components and measurement of pCO2, pO2 , pH , glucose concentration. Other methods of evaluation are BacT/Alert (BioMerieux) and eBDS (Pall) were utilized nowadays for to detect bacterial contamination. For ultrafast and specific results, molecular technologies, based on the detection of ribosomal RNA of a wide variety of bacteria in a platelet contaminated sample containing 1–10 CFU/mL, have also been evaluated but molecular techniques are expensive. Pathogen reduction techniques is helpful as they make bacteria and viruses inactive in the contaminated platelet concentrates. Two most common methods are generally utilized for inactivation of platelets are psoralen and riboflavin-based method. Results and Conclusion: Institute has to establish their own measures to decrease the possible platelet concentrates contamination. Pathogen inactivation techniques will be the next revolutionary aspect in blood banking.